Implementasi Rumah Sederhana Sehat pada Perumahan Puri Kencana, Wagir, Kabupaten Malang - Rivaldi; Ary Deddy Putranto ST., MT. (Jurnal Mahasiswa Departemen Arsitektur, 2024)
Housing is a collection of houses as part of settlements, both located in urban and ruralareas, which are equipped with public infrastructure, facilities and utilities as a result ofefforts to fulfill habitable houses which were built as basic human needs that must be met forfamily needs, as a place to live. stay.Residential housing should meet various requirements for a healthy home which canaffect the quality of the building structure or other related matters.The condition of housing or settlements is something that needs to be paid attentionto and must be monitored jointly by a group of people living in the settlement with assistancefrom the competent government as a responsible institution.Puri Kencana Wagir Housing in Malang Regency is a simple housing complex that isdeveloping rapidly and offers simple housing solutions for various levels of society. Thishousing complex has appeal to many families looking for an affordable place to live.However, to ensure that this housing meets the standards of healthy housing needs, acomprehensive analysis of the condition of existing simple houses is needed, especially thosecurrently being developed by Puri Kencana Wagir Housing.This research resulted in how concepts related to Simple Healthy Homes wereimplemented at Puri Kencana Wagir Housing.Keywords: Implementation of a Simple Healthy House, RSS Concept.